Unity, Objectivity, and the Passivity of Experience. (16th December 2016) - Gomes, Anil
Abstract: In the section 'Unity and Objectivity' of The Bounds of Sense, P. F. Strawson argues for the thesis that unity of consciousness requires experience of an objective world. My aim in this essay is to evaluate this claim. In the first and second parts of the essay, I explicate Strawson's thesis, reconstruct his argument, and identify the point at which the argument fails. Strawson's discussion nevertheless raises an important question: are there ways in which we must think of our experiences if we are to self‐ascribe them? In the third part of the essay, I use Kant's remarks concerning the passivity of experience to suggest one answer to this question: in self‐ascribing experiences, we must be capable of thinking of them as passive to their objects. This can be used to provide an alternative route from unity to objectivity.